ANALISIS KESUKSESAN WEBSITE KEDOKTERAN UNIVERSITAS HANGTUAH SURABAYA DENGAN MENGGUNAKAN MODEL DELONE DAN MCLEAN BERDASARKAN PERSEPSI MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS HANGTUAH SURABAYA - revianto, tito; tiowati, Sulis; rahmawati, endra (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2018)
Faculty of Medicines Website, Hang Tuah University began to be designed and built in 1987. The goal is to assist students in terms of lectures. Faculty of Medicines Website has started to provide the internet access for its users and developed online service since 1987 until today. Based on interview data of Faculty of Medicines students as many as 30 (thirty) respondents, 24 (twentyfour) respondents said that the Website is less attractive. In order to reduce the risk of not successful implementation of the Website then in this study was analyzed by using Delone and McLean Methods. By doing this research, the Management of the Website may know what factors are important in the development process and as an evaluation material for the Management of the Website